(untitled) (Journal of Atomic and Molecular Sciences, 2016)
Three-Coulomb-wave (3C) model is applied to study the single ionization of helium by 16MeV O^7+ impact in the scattering plane. Fully differential cross sections (FDCS) is presented for the different momentum transfers. Our theoretical results are compared with the recent experimental data and the results of continuum distorted-wave eikonal-initial-state (CDW-EIS). It is shown that the 3C calculations qualitatively reproduce the experimental peak structure, especially at smaller momentum transfers.